Organization development : the process of leading organizational change - Anderson, Donald L., 1971- (2020)
"Organization Development: The Process of Leading Organizational Change, FifthEdition offers a comprehensive look at individual, team, and organizational change, covering classic and contemporary organization development techniques. Today's practitioners seek a solid foundation that is academically rigorous, but also relevant, timely, practical, and grounded in OD values and ethics. In this bestselling text, author Donald L. Anderson provides students with the organization development tools they need to succeed in today's challenging environment of increased globalization, rapidly changing technologies, economic pressures, and evolving workforce expectations"--
Includes bibliographical references (pages 439-470) and index.
Keywords: Organizational change